2008
DOI: 10.1667/rr1204.1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Antioxidants Protect Hematopoietic Cells and Improve Animal Survival after Total-Body Irradiation

Abstract: The purpose of this study was to determine whether a dietary supplement consisting of Lselenomethionine, vitamin C, vitamin E succinate, α-lipoic acid and N-acetyl cysteine could improve the survival of mice after total-body irradiation. Antioxidants significantly increased the 30-day survival of mice after exposure to a potentially lethal dose of X rays when given prior to or after animal irradiation. Pretreatment of animals with antioxidants resulted in significantly higher total white blood cell and neutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
72
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 66 publications
11
72
0
Order By: Relevance
“…Significant reduction in haematological indices following irradiation reported here is consistent with earlier reports on radiation-induced ablation of bone marrow [26,27]. Irradiation severely depleted reticulocytes, WBCs, neutrophils, lymphocytes, platelets and haematocrit counts, an effect that persisted 21-28 days after exposure.…”
Section: Discussionsupporting
confidence: 92%
“…Significant reduction in haematological indices following irradiation reported here is consistent with earlier reports on radiation-induced ablation of bone marrow [26,27]. Irradiation severely depleted reticulocytes, WBCs, neutrophils, lymphocytes, platelets and haematocrit counts, an effect that persisted 21-28 days after exposure.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, although many studies have demonstrated the antimutagenic activity of ascorbic acid (CAI; KOROPATNICK; CHERIAN, 2001;ALY;DONYA, 2003;ORTMANN et al, 2004;JAGETIA;RAJANIKANT;RAO, 2007;MOZDARANI;GHORAEIAN, 2008;WAMBI et al, 2008;ASSAYED;KHALAF;SALEM, 2010), in some cases, it can act as a co-mutagenic leading to the generation of oxygen radicals that induce sister chromatid exchanges and other cytogenetic damage (KONAPACKA; WIDEL; REZESZOWSKA-WOLNY, 1998;KAYA et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Furthermore, dietary AOX supplementation prior to or after exposure to GR TBI was an effective countermeasure in limiting hematopoietic cell depletion, promoting hematopoietic cell recovery, and ultimately, improving mice survival. 1 Proton radiation (PR) has generated interest for its capacity to selectively increase radiation dose to the tumor while lowering the dose to surrounding normal tissues. In a subsequent experiment, the same dietary AOX supplementation also significantly improved 30-day survival of mice when administered after PR TBI.…”
Section: Resultsmentioning
confidence: 99%